PRIMARY CULTURES OF DISSOCIATED SYMPATHETIC NEURONS : III. Changes in Metabolism with Age in Culture - Mains, Richard E. (The Rockefeller University Press, 1973)
Several biochemical parameters of dissociated sympathetic neurons from superior cervical ganglia of the newborn rat were monitored as a function of age in culture. The neurons, which were grown in the virtual absence of non-neural cells, displayed a striking increase in their ability to synthesize and accumulate catecholamines. This capacity increased 50-fold during a 3-wk period in vitro, after which it appeared to reach a steady level. The major change took place during the second week. The time course of this change was not affected by plating the neurons at a higher cell density. The change in the catecholamine metabolism was far greater in magnitude and quite different in time course from the overall growth of the cells which was monitored by the incorporation of radioactive tyrosine into protein, lipid synthesis from radioactive choline, and incorporation of radioactive uridine into acid-precipitable material. Of the total tyrosine used by the cultures, the proportion devoted to catecholamine synthesis increased to 25% (a 10-fold rise) during the 3-wk period. This changing pattern of metabolism in the cultures suggested a process of maturation which may be similar to neuronal development in vivo.